Hubungan Intensitas Bermain Game Mobile Online dengan Kemampuan Motorik Siswa Sekolah Menegah Atas Negeri 1 Berastagi - Janwar Frihasan Sinuraya; Julius Boy Nesra Bagismata Barus (Mahesa Research Center, 2022)
The purpose of this study was to evaluate the relationship between the intensity of playing mobile online games with the motor skills of class XI students at SMA Negeri 1 Berastagi, Karo Regency. This research is a correlational study. The population used were students of class X and XI. The samples used were students of class X and XI of SMA Negeri 1 Berastagi, Karo Regency, amounting to 75 students who were taken by using the census technique. The intensity instrument for playing mobile online games is a questionnaire, and motor skills are Barrow motor ability test which includes tests (1) standing board jump, (2) zig-zag run, (3) medicine ballput, (4) softball throw, (5) wall pass, and (6) a 60 yard dush or 55 meter run. Data analysis using product moment correlation test. The results showed that there was a strong relationship between the intensity of playing mobile online games with the motor skills of class X and XI students at SMA Negeri 1 Berastagi, with rx.y = -0.531 > r(0.05)(75) = 0.224 and a significance value of 0.000. < 0.05. It can be concluded that the relationship between the intensity of playing mobile online games and students' motor skills is negative, implying that the greater the intensity of playing mobile online games, the worse the students' motor skills.